Partisipasi Masyarakat Dalam Pengelolaan Sampah Masa Pandemik Covid 2019 Di RT 026/ RW 006 Kelurahan Oebufu Kecamatan Oebobo Kota Kupang - Muntasir Muntasir; Riski Arisando Bahan; Marisa Sinlae; Aldi Benggu; Hetgen Palabuan (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Handling household waste requires serious attention from various parties to protect the environmental ecosystem from being damaged. Community service provides benefits for the active role of the community in handling household waste with the target of community participation at the level of understanding the knowledge, attitudes, and behavior in handling waste. Community service methods by conducting lectures, socialization, counseling, and waste management; demonstration of organic and inorganic waste containers; simulation videos; physical activity in the form of community service; non-physical activities in the form of socialization and distribution of leaflets; assistance to residents on waste management; evaluation of activities, and sustainability of activities. Presentation of devotion in a descriptive and narrative manner. The results of the activity show that the participation of community members in RT 026 RW 006 Oebufu Village, Oebobo Kupang District in controlling household waste with a system for handling used materials, waste or household waste materials showed in activities community service, the desire to get information and willing to be invited in the evaluation and assistance of waste management. The percentage of waste management knowledge before the intervention reached 81%, namely in the good category, after the intervention, the knowledge of the residents increased to 94%. Attitudes about waste management before the intervention reached 77%, namely in the good category, after the intervention increased to 89%. Behavior regarding waste management before the intervention reached 51%, namely in the good category, after the intervention increased to 58%.